The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1029/2010wr010197
|View full text |Cite
|
Sign up to set email alerts
|

Temporal inequality in catchment discharge and solute export

Abstract: [1] A framework is developed for characterizing the temporal inequality of stream discharge and solute loads to receiving waters using Lorenz diagrams and the associated Gini coefficient, G. These descriptors are used to illustrate a broad range of observed flow variability with a synthesis of multidecadal flow data from 22 rivers in Florida. Multidecadal phosphorus load data from four of the primary tributaries to Lake Okeechobee, Florida, and sodium and nitrate load data from nine of the Hubbard Brook, New H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(100 citation statements)
references
References 44 publications
(90 reference statements)
5
95
0
Order By: Relevance
“…Recently, the concept has been applied to other research fields, such as inequalities in global water use (Seekell et al, 2011) and plant size and fecundity (Damgaard and Weiner, 2000), and temporal inequalities in catchment discharge (Jawitz and Mitchell, 2011;Masaki et al, 2014). Rajah et al (2014) used the Gini coefficient to analyze the distribution of precipitation and changes in precipitation.…”
Section: Temporal Inequality Indicesmentioning
confidence: 99%
“…Recently, the concept has been applied to other research fields, such as inequalities in global water use (Seekell et al, 2011) and plant size and fecundity (Damgaard and Weiner, 2000), and temporal inequalities in catchment discharge (Jawitz and Mitchell, 2011;Masaki et al, 2014). Rajah et al (2014) used the Gini coefficient to analyze the distribution of precipitation and changes in precipitation.…”
Section: Temporal Inequality Indicesmentioning
confidence: 99%
“…Recent work by Jawitz and Mitchell (2011) has demonstrated that considering the ratio of the variances of log-transformed loads and log-transformed flows may provide improved understanding of the interplay between concentrations and loads in relation to chemostasis. By adopting such an approach, analytical solutions for the solute export equations describing the correlation between mass fluxes and discharge (such as that seen in Fig.…”
Section: Relationship Between Observed and Modeled C Dynamicsmentioning
confidence: 99%
“…A constant pattern exhibits little directional changes in C with changes in Q (b~0), as observed for Ca 2+ and other ions with geogenic sources [Godsey et al, 2009;Thompson et al, 2011]. We define chemostatic and chemodynamic solute export regimes (Figures 1b and 1c and S1), based on the relative temporal variability in C compared to Q [Jawitz and Mitchell, 2011;Thompson et al, 2011]. We define chemostatic and chemodynamic solute export regimes (Figures 1b and 1c and S1), based on the relative temporal variability in C compared to Q [Jawitz and Mitchell, 2011;Thompson et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…Note that these authors have referred to b~0 as "chemostatic," but we prefer "constant" because we reserve the former term for export regimes, which we define below as differentiated from C-Q patterns. Chemostatic export regimes have been observed for geologic weathering products such as Ca +2 , Mg 2+ , and K + [Godsey et al, 2009;Herndon et al, 2015;Musolff et al, 2015], as well as anthropogenically mediated solutes, such as NO 3 À and PO 4 À [Basu et al, 2010;Jawitz and Mitchell, 2011], and animalborne hormones [Gall et al, 2016]. In chemostatic export regimes, the coefficient of variation (CV) is low for C relative to Q, with CV C /CV Q ≤ 0.5 independent of slope b. Consequently, exported solute load variance CV L is dominated by discharge variance which reflects in CV L /CV Q~1 .…”
Section: Introductionmentioning
confidence: 99%